'Fear is What Weighs Most...' Experiences of Women in Situations of Violence in Accessing Support Services in Brazil - Machado, Ana Luiza; Muller, Miriam; Van Wie, Sara (World Bank, Washington, DC, 2020)
This paper seeks to fill a knowledge gap relative to the low uptake of services for women living in situations of violence. The phenomenon is observed in many countries, including in Brazil, despite its robust legal framework to prevent and protect women from domestic violence. Through qualitative research, this paper explores the experience of women survivors of violence against women (VAW) in seeking help to exit abusive relationships, with the aim of identifying avenues to strengthen service delivery and violence prevention policies. The experiences of research participants demonstrate that a complex set of issues related to social norms, individual agency and institutional weaknesses serve as strong barriers for service uptake. These include women's personal preparedness to seek support; the catalyzing or constraining function that families, friends, peers and people in authority can play; external barriers to accessing services; and the availability and quality of services in different settings. Data from this research also highlight the importance of psycho-social support services that help survivors make informed decisions about how to exit abusive relationships, to rebuild their emotional stability and self-esteem, establish economic autonomy, pursue justice, and ultimately reconstruct their lives.